FORMATION OF AN INCLUSIVE MODEL OF PHYSICAL EDUCATION FOR STUDENTS WITH DISABILITIES WHO ARE WAR VETERANS IN HIGHER EDUCATION INSTITUTIONS - Blavt, Oksana (Mountain School of Ukrainian Carpaty, 2023)
The relevance of the study is determined by the urgent need of the educational community to provide a full opportunity to receive higher education for participants in hostilities, and above all for war veterans, among whom there are many students with disabilities. The purpose of the work is to identify the key foundations of the formation of an inclusive physical education model for war veteran students in higher education institutions. Research methods: theoretical analysis, systematization, comparison of different views on the investigated problem, generalization of data from scientific and methodological, and special literature. It was investigated that the challenges related to the implementation of inclusive education, which faced the education system of Ukraine, are identical to European systems. The implementation of foreign experience in the domestic educational process is a creative combination of key components of corrective development and the interaction of participants in the educational process (teachers and students with disabilities, war veterans) in the course of inclusive physical education aimed at overcoming the effects of the war to eliminate violations in their health. It was found that efforts should be directed to the justification and creation of effective models of inclusive physical education, organized based on modern innovative general scientific and special technologies, theory, methods and practice of physical culture, which would ensure a high level of physical activity of students with disabilities who are war veterans in the process of their their adaptation in the environment of the educational institution would contribute to their health and achievement of the predicted results in the course of their higher education. The directions of implantation of progressive ideas in the process of formation of an inclusive model of physical education for students with disabilities who are war veterans in higher education institutions are singled out. These include training physical education specialists who fully possess inclusive competence; updating the content of methods in the field of inclusive physical education; targeted educational and informational work to develop the need for physical self-improvement and health care among students with disabilities who are war veterans; development of motivation to engage in physical education of students with disabilities who are war veterans; support of the organization of students with disabilities who are war veterans in their physical education on an equal basis with all participants in the educational process; creation of centers of physical culture and sports orientation for students with disabilities who are war veterans in institutions of higher education.